Ground heave due to line injection sources. (July 2015) - Kim, Jueun; Selvadurai, A.P.S.
Abstract: This paper examines the geomechanical effects resulting from the injection of a non-reactive fluid along a line segment located at the interior of a poroelastic halfspace. The mechanical behaviour of the geologic medium is described using Biot's classical theory of poroelasticity. The mathematical solutions for the surface heave associated with a point injection source are used to develop results for the ground heave associated with both vertically-aligned and horizontally-aligned line injection sources of constant intensity and finite length. The results obtained from the mathematical analysis are used to benchmark computational results for analogous problems. Highlights: An analytical solution for the poroelastic problem associated with a line injection sources is developed. Numerical results that can be used as a first approximation of ground heave for different line injection lengths are presented. The potential of failure development at the injection zone is examined. Provides validation of a computational approach.